Cecilia attempts to prove that 0 = 1 . This was her proof:
− 2 0 1 6 − 3 6 4 2 − 4 ⋅ 9 4 2 − 4 ⋅ 9 + 4 8 1 4 2 − 2 ⋅ 4 ⋅ 2 9 + ( 2 9 ) 2 ( 4 − 2 9 ) 2 ( 4 − 2 9 ) ( 4 − 2 9 ) + 2 1 0 = − 2 0 = 2 5 − 4 5 = 5 2 − 5 ⋅ 9 = 5 2 − 5 ⋅ 9 + 4 8 1 = 5 2 − 5 ⋅ 9 + ( 2 9 ) 2 = ( 5 − 2 9 ) 2 = ( 5 − 2 9 ) = ( 5 − 2 9 ) + 2 1 = 1
Which is the first step where she made a mistake? Assume that the first line of the equation ( − 2 0 = − 2 0 ) is the first step.
Signs: a ⋅ b ⋅ c = ( a × b × c ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
The square root function is defined as x ² = ∣ x ∣ 4 − 2 9 < 0 , So we actually have ( 4 − 2 9 ) ² = ∣ ∣ ∣ ∣ 4 − 2 9 ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ − 2 1 ∣ ∣ ∣ ∣ = + 2 1 = 2 9 − 4 Therefore, the mistake occurs in the 7th step where Cecilia wrongly evaluates ( 4 − 2 9 ) ² as 4 − 2 9